THE APPLICATION OF TAJWID LEARNING MODEL TO DEVELOP THE READING ABILITY OF AL-QUR'AN (Case study at the TPQ Barokah Gonilan, Kartasura, Sukoharjo 2019) - Ririn Naila Rahmawati (Universitas Muhammadiyah Surakarta, 2019)
Thih reasearch describe that TPQ Barokah is different from other common TPQ. In the TPQ Barokah using the system where it combines the way of the reading Qur’an using the method with pronunciation according to the correct science rules. The purpose of this research is to obtain information about the implementation of the learning of the Qur'an in the application of science tajwid into the recitation of the Qur'an to develop the ability to read the Qur'an in the students of the TPQ Barokah Gonilan. The Methodology research. The results of this study showed that the study of the Qur'an in the TPQ Barokah Gonilan for the application of Tajwid science is different in accordance with the result of its class. In the first meeting the teacher more emphasis on the understanding of science material tajwid and for the meeting of the two teachers more multiply reading practice of the Qur'an so that the ability to read the Qur'an students continues to evolve.